POTENSI EARNINGS MANAGEMENT MEMEDIASI FINANCIAL DISTRESS - Hadriana Hanafie; Nur Hikmah; Ahmad Efendi; Muhammad Wahyuddin Abdullah (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to examine the cash conversion cycle and intellectual capital against financial distress through earnings management. The research population includes manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018. Determination of the sample was based on the purposive sampling method with a total sample of 110. The research data is secondary data accessed through www.idx.co.id and http://finance.yahoo.com. The analysis technique uses path analysis to determine the direct and indirect effects between research variables. The results showed that the cash conversion cycle has a significant positive effect on earnings management, intellectual capital has a significant negative effect on earnings management, and earnings management has a significant positive effect on financial distress. Cash conversion cycle has a significant positive effect on financial distress through earnings management and intellectual capital has a significant negative effect on financial distress through earnings management. Keyword: Cash Conversion Cycle, Intellectual Capital. Earnings Management, Financial Distress